Mini-gastric Bypass Complications and the Value of the Preoperative Neutrophil to Lymphocyte Ratio in Early Prediction of Complications - Dogan, Fadli; Dincer, Mursit (Coll Physicians & Surgeons Pakistan, 2021)
Objective: To describe the short-term results of mini-gastric bypass (MGB), the complications in patients who underwent mini-gastric bypass surgery (MGB), and evaluate the value of the neutrophil to lymphocyte ratio (NLR) in predicting complications at an early stage. Study Design: A descriptive, analytical study. Place and Duration of Study: Elazig Medical Park Hospital, Elazig, Turkey from January, 2016 to July 2019. Methodology: Data of patients who had undergone MGB for morbid obesity at the Department of Surgery, Medical Park Hospital, Elazig, Turkey from January 2016 to July 2019 were retrospectively evaluated. Demographic characteristics, preoperative body weight, body mass index (BMI), weight change after surgery, and postoperative complications were evaluated. The collected data were statistically analysed. The Kolmogorov-Smirnov and Shapiro-Wilk tests were used to evaluate the data distribution. Results: A total of 95 patients were included in the study. The median preoperative BMI was 40.7 kg/m(2) (40.2-42.5), the median NLR was 2.1 (1.5-2.8), and the median length of hospital stay was 4.0 (3.0-4.0) days. In univariate analysis, age, gender, preoperative baseline BMI or preoperative NLR were not statistically significant related to the presence of postoperative complications. There was a statistically significant difference in BMI, depending on different measurement times during the follow-up period (p< 0.001). Conclusion: MGB is an effective procedure in obesity and diabetes surgery. Complications with high morbidity and mortality might be seen, although at low rates. Although NLR's efficacy is low in predicting MGB complications, it may be a useful parameter in a large series.
Keywords: Bariatric surgery; Complications; Mini-gastric bypass; Morbid obesity